2016
DOI: 10.2174/1381612822666160202141845
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the dsRNA-Activated Protein Kinase PKR in Mitochondrial Dysfunction and Inflammatory Stress in Metabolic Syndrome

Abstract: This review highlights recent findings in PKR-mediated metaflammation and its association with the onset of metabolic syndrome in both human and animal models, with a focus on the molecular and biochemical pathways that underlie the progression of obesity, insulin resistance, and type-2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…PKR is a key constituent of the metaflammasome, activated by nutrients such as fatty acids and by ER stress [147]. The interaction between the PKR, and inflammatory kinases, such as IKK and JNK, IRS1 has also been reported [148]. The absence of PKR leads to decreased activation of JNK and IKKβ which are key kinases in the development of insulin resistance.…”
Section: Rna-activated Protein Kinase (Pkr)mentioning
confidence: 99%
“…PKR is a key constituent of the metaflammasome, activated by nutrients such as fatty acids and by ER stress [147]. The interaction between the PKR, and inflammatory kinases, such as IKK and JNK, IRS1 has also been reported [148]. The absence of PKR leads to decreased activation of JNK and IKKβ which are key kinases in the development of insulin resistance.…”
Section: Rna-activated Protein Kinase (Pkr)mentioning
confidence: 99%
“…24). These PKR-associated processes support the relevance of PKR's regulation; in fact, numerous studies have found PKR to be dysregulated in most type of cancers, neurodegenerative diseases, metabolic disorders and other pathologies (Refs 8,25). Whereas PKR is recognised for its negative effects on neurodegenerative diseases, the role of PKR activation in cancer is complex and remains controversial (reviewed in Ref.…”
Section: Introductionmentioning
confidence: 89%
“…HRI) [ 6 , 29 ]. PKR has been implicated in a broad spectrum of infectious and inflammatory processes in addition to its well-known antiviral response [ 30 33 ]. PKR is activated in murine colonic epithelial cells during DSS-induced colitis.…”
Section: Cellular Stress Signaling In Gastrointestinal Tractmentioning
confidence: 99%